Experimental study on combustion pressure oscillation of soybean bio diesel oil - Peng, Ma; Huili, Liu; Shengyong, Liu (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: The principal objectives of this study were to examine in-cylinder combustion pressure oscillation characteristics of soybean biodiesel in time domain and time-frequency domain, and their influences on the control and operational parameters, such as injection timing, exhaust gas recirculation (EGR) ratio, engine load and engine speed. In this study, the combustion pressure oscillation characteristics of biodiesel engine for various injection timing, EGR ratio and engine speed were investigated. The corresponding relation of pressure characteristics in the time domain and frequency domain were obtained. The results showed that the pressure oscillation and peak pressure rise acceleration occurred mainly in the diffusion combustion, and the peak pressure rise rate located in the premixed combustion. The in-cylinder pressure level curve can be divided into three stages. The pressure levels of stage 1, stage 2 and stage 3 represent the peak in-cylinder pressure, the maximum amplitude of pressure rise rate and pressure rise acceleration, respectively. As the injection timing retards, the pressure levels of stage 1 and stage 3 decrease gradually. The pressure level curve of stage 3 with 25º before top dead center (BTDC) is the highest and the oscillation is the most significant. It is worth noting that the location of each stage with various operate conditions is not fixed. At 0.41 MPa indicated mean effective pressure (IMEP), with the increase of EGR rate, the pressure levels of stage 1 and stage 2 decrease gradually. The pressure level curve of stage 3 and the maximum amplitude of pressure rise acceleration with 0% EGR rate are the highest. The oscillation with 0% EGR rate is the most significant at 0.41 MPa IMEP. Compared to 0.41 MPa IMEP, the frequency bands of stage 1 and stage 2 at 1.1 MPa IMEP are relatively low due to the soft combustion in the cylinder. As EGR rate increases, the pressure level of stage 1 decreases, and those of stage 2 and stage 3 increase gradually. The oscillation with 30% EGR rate is the most significant. With the increase of engine speed, the pressure levels of stage 1 and stage 2 decrease, and move to the low frequency. The pressure level in the high frequency domain at 1600 r/min is less than that at 1100 r/min, and the combustion process is smooth. Keywords: combustion pressure oscillation, soybean biodiesel, injection timing, exhaust gas recirculation, engine speed DOI: 10.3965/j.ijabe.20160906.1680 Citation: Ma P, Liu H L, Liu S Y. Experimental study on combustion pressure oscillation of soybean bio diesel oil. Int J Agric & Biol Eng, 2016; 9(6): 156-166.